Cellulose‐Based Nanogenerators: An Overview of Cellulose‐Based Nanogenerators (Adv. Mater. Technol. 3/2021). Issue 3 (8th March 2021) - Annamalai, Pratheep K.; Nanjundan, Ashok Kumar; Dubal, Deepak P.; Baek, Jong‐Beom
Abstract : Cellulose biomass is an inexpensive raw material for fabricating the technological products and devices for a sustainable future and environment. In the article 2001164, Ashok Kumar Nanjundan, Jong‐Beom Baek, and co‐workers show how cellulose can be modified into various morphologies and utilized to produce cost‐effective nanogenerators that can exploit the microenergies into utilizable electricity and self‐powered systems. This back cover features the hierarchical nature of cellulose and various applications of nanogenerators.